The effect of changes in the replacement rate on partial retirement in Sweden - Erik Glans (Uppsala University, Department of Economics, 2008)
Knowledge about how elderly workers react to changes in pension benefits is important in guiding the design of social security systems. This paper contributes to this knowledge by examining the effect of changed replacement rates on part-time retirement behaviour in Sweden. During the 1980s, older workers had the option of partial retirement with an income replacement of 65 percent. The replacement rate was lowered to 50 percent in 1981 and subsequently increased back to 65 percent in 1987. Estimates using a linear probability model with register data from the LINDA database suggest that fewer men and women chose part-time retirement after the reduction in benefit levels in 1981. There was an approximate 4 percentage point drop in the partial retirement propensity among eligible 60-year old men, and a 5.7 percent drop among women. This corresponds to proportional reductions in the retirement propensity by about 29 and 36 percent respectively. The probability of part-time retirement increased among men by about 3.5 percentage points once benefit levels were increased again, whereas the partial retirement probability of women remained largely unchanged.
urn:nbn:se:uu:diva-86607
Keywords: H55; J26; 330; Retirement; Labour supply; Pensions; Gesetzliche Rentenversicherung; Altersvorsorge; Flexible Altersgrenze; Rentenpolitik; Wirkungsanalyse; Schweden